2013
DOI: 10.1051/0004-6361/201220582
|View full text |Cite
|
Sign up to set email alerts
|

CALIFA, the Calar Alto Legacy Integral Field Area survey

Abstract: We present the first public data release (DR1) of the Calar Alto Legacy Integral Field Area (CALIFA) survey. It consists of science-grade optical datacubes for the first 100 of eventually 600 nearby (0.005 < z < 0.03) galaxies, obtained with the integral-field spectrograph PMAS/PPak mounted on the 3.5 m telescope at the Calar Alto observatory. The galaxies in DR1 already cover a wide range of properties in color-magnitude space, morphological type, stellar mass, and gas ionization conditions. This offers the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(116 citation statements)
references
References 38 publications
1
115
0
Order By: Relevance
“…To reduce the effects of the vignetting on blue part (up to ∼ 4200Å) of the V500 data in some parts of the FoV (see Fig. 11 of Husemann et al (2013)), we combine both setups producing a so-called COMBO datacube. The V1200 spectral resolution is degraded to match the V500 data.…”
Section: Caha 2d-spectroscopic Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the effects of the vignetting on blue part (up to ∼ 4200Å) of the V500 data in some parts of the FoV (see Fig. 11 of Husemann et al (2013)), we combine both setups producing a so-called COMBO datacube. The V1200 spectral resolution is degraded to match the V500 data.…”
Section: Caha 2d-spectroscopic Observationmentioning
confidence: 99%
“…For the remaining wavelength range, the blue part corresponds to the matched V1200 cube and the red part, to the right of the overlapping region, to the original V500 datacube. More details of the reduction process can be found in Husemann et al (2013), García-Benito et al (2015) and Sánchez et al (2016). The final datacube, corrected for Galactic extinction, fully covers the optical range from 3700 to 7300Å.…”
Section: Caha 2d-spectroscopic Observationmentioning
confidence: 99%
“…Observations were carried out at low (V500, R ∼ 850 and spectral coverage between 3750 and 7500 Å) and medium (V1200, R ∼ 1700 and spectral coverage between 3700 and 4200 Å) spectral resolution, with each galaxy covered by two to three dithered exposures per mode. Once the raw data were taken, they were processed by the CALIFA pipeline (Husemann et al 2013), which removes cosmic rays, carries out flux calibration and extinction corrections, and interpolates the data onto a 78 × 72 grid. All processed data cubes were made public and provided to the community via regular Data Releases, the final one being the DR3 (Sánchez et al 2016).…”
Section: The Califa Surveymentioning
confidence: 99%
“…They compared their kinematical PAs with the photometric PAs from the HyperLeda 1 database and found that the offset between the photometric and kinematic position angles, ∆PA, is observed in both isolated as well as in interacting galaxies. Barrera-Ballesteros et al (2014 determined the offsets between the photometric and kinematic position angles for isolated and interacting or merging galaxies measured by the Calar Alto Legacy Integral Field Area 1 http://leda.univ-lyon1.fr/ (CALIFA) survey (Sánchez et al 2012;Husemann et al 2013;García-Benito et al 2015). They found that ∆PA > 21 • for 43% of the interacting or merging galaxies and for 10% of the isolated galaxies in their sample.…”
Section: Introductionmentioning
confidence: 99%